Pembiayaan Pendidikan Formal Tingkat Dasar - Kemal Masjhur; Neti Karnati (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
According to the constitutional mandate, it is obligatory to provide education for citizens. To provide quality education, a large amount of funding is needed. The education budget of 20% of the APBN is not sufficient to provide education for all citizens who have the right to education. The private sector is expected to participate in providing education. The government provides financial assistance to support private schools that need it. The research was conducted qualitative methods. Data collection was carried out through literature study, then completed with interviews and observations, to see the conditions that occurred. Funding sources for basic level formal education institutions consist of school tuition, government assistance (BOS) and assistance from the community. However, not all elementary schools can take advantage of these three sources of funding. Public schools do not charge tution, there are private schools that have not or have not yet received BOS. Based on these sources of funds, schools prepare estimates of cash receipts and disbursements. Then a pro forma balance statement is prepared, to see the profit or loss that will be experienced. After that, schools already have budget implementation guidelines or RAPBS.